EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THREE STEPS INTERVIEW (TSI) DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SAINTIFIK PADA MATERI FUNGSI DITINJAU DARI MULTIPLE INTELLIGENCES SISWA KELAS VIII SMP NEGERI SE-KABUPATEN SUKOHARJO - Maharani, Rizqona; Mardiyana, Mardiyana; Usodo, Budi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purpose of this study wasÂ  to determine the effect of the learning models on the learning achievement in mathematics viewed from the studentsâ multiple intelligences. The learning models compared were the cooperative learning of the three steps interview (TSI) type with scientific approach, think pair share (TPS) model type with scientific approach, and classical learning withÂ  scientific approach. The type of this study was quasi experimental study with a 3x3 factorial design. The population was all grade 8 students of Secondary Schools in Sukoharjo Regency. Instruments used for data collection were mathematics achievement test and multiple intelligences questionnaire. The data analysis technique used was the two-way ANOVA with unequal cell. Based on the hipothesis, the results of the study could be concluded as follows. (1) TSI with scientific approach got better learning achievement than TPS with scientific approach and classical with scientific approach. In addition, TPS with scientific approach got better learning achievement than classical with scientific approach. (2) Students with logical mathematical intelligence got better achievement than students with linguistic intelligence and students with interpersonal intelligence, students with linguistic intelligence got better achievement than students with interpersonal intelligence. (3) Viewed from learning models, students with logical mathematical intelligence got better achievement than students with linguistic intelligence and students with interpersonal intelligence. However, students with linguistic intelligence got better achievement than students with interpersonal intelligence. (4) Viewed multiple intelligencesâ categories, TSI model with scientific approach got better achievement than TPS with scientific approach and classical with scientific approach. However, TPS with scientific approach got better achievement than classical with scientific approach.Keywords: Three Steps Interview (TSI), Think Pair Share (TPS), Classical Learning, Scientific Approach, and Multiple Intelligences.